2009
DOI: 10.1542/peds.2009-0213
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Cardiometabolic Risk Factors in the United States Adolescent Population

Abstract: OBJECTIVE Evidence on the association of vitamin D with cardiovascular risk factors in youth is very limited. We examined whether low serum vitamin D levels [25(OH)D] are associated with cardiovascular risk factors in US adolescents aged 12–19 years. METHODS Cross-sectional analysis of 3,577 fasting, nonpregnant adolescents without diagnosed diabetes who participated in the 2001–2004 National Health and Nutrition Examination Survey (NHANES). Risk factors for cardiovascular disease measured using standard met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
250
11
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(302 citation statements)
references
References 52 publications
21
250
11
20
Order By: Relevance
“…A significant association between 25(OH)D and CVD risk factors in children and adolescents would suggest that successful vitamin D supplementation has the potential to improve CVD risk markers and to lower the risk of CVD in adulthood. However, compared with adults, the associations between vitamin D and MetS as well as its individual CVD risk factors have not been fully explored in children (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). We therefore conducted a crosssectional study to examine the association of serum vitamin D levels with the MetS, its individual components, and early atherosclerotic abnormalities in a large sample of Italian overweight/obese and normalweight children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…A significant association between 25(OH)D and CVD risk factors in children and adolescents would suggest that successful vitamin D supplementation has the potential to improve CVD risk markers and to lower the risk of CVD in adulthood. However, compared with adults, the associations between vitamin D and MetS as well as its individual CVD risk factors have not been fully explored in children (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). We therefore conducted a crosssectional study to examine the association of serum vitamin D levels with the MetS, its individual components, and early atherosclerotic abnormalities in a large sample of Italian overweight/obese and normalweight children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…43 Data from the National Health and Nutrition Examination Survey (NHANES) 2001-2004 concluded that low 25(OH)D levels were associated with hyper-tension, hyperglycemia, and metabolic syndrome in the United States adolescent population. 44 Similarly, a study in Caucasian children also found that central obesity, hypertension, hypertriglyceridemia, low HDL-C levels, and metabolic syndrome were associated with low 25(OH)D levels. 45 Despite the fact that in our study vitamin D was assessed only by nutritional intake, our results are in line with those of these investigations by showing that adolescents in the lowest vitamin D intake quartile group had an OR of 3.35 for high cardiometabolic risk score compared with the highest vitamin D intake quartile group after adjustment for several confounders.…”
Section: Discussionmentioning
confidence: 93%
“…Em adolescentes obesos, baixas concentrações de vitamina D também têm sido associadas com níveis reduzidos de HDL-c [43] e elevados de triglicerídeos e do índice homeostatic model assessment para resistência à insulina (HOMA-IR) [44]. Um estudo realizado com 3.577 adolescentes americanos com idades entre 12 e 19 anos encontrou maior chance de hipertensão arterial e SM para os indivíduos no menor quartil do nível sérico de 25 (OH) D, em comparação com o maior quartil, independentemente da adiposidade corporal [45].…”
Section: Discussionunclassified